Evaluation of the Biological and Wound Healing Activities of Centaurea virgata Lam. - AKSOY, HALİL (MARMARA UNIV, INST HEALTH SCIENCES, 2020)
Objective: Plants have significant potential effects in treating wounds. Some plants are also used in traditional medicine for their wound healing properties. The aim of this study was to investigate the antioxidant and in vitro wound healing activities of Centaurea virgata. Methods: The antioxidant activities ofextracts were examined by 2,2-diphenyl-1-picryl-hydrazyl (DPPH) and 2,2-azinobis-(3-ethylbenzothiazoline-6-sulphonic acid (ABTS) methods. The total phenolic content was determined using the Folin-Ciocalteu reagent (FCR) method. In addition, the antiproliferative activity of different extracts on fibroblast cells was performed by MTT method and in vitro wound healing activity of ethanol extract of C. virgata was determined by scratch assay. Results: Ethyl acetate fraction of ethanol extract of C. virgata (CVEA) had the highest DPPH radical scavenging activity with an IC50 value of 138.7 mu g/mL. According to ABTS results, it was determined that the CVEA had a stronger radical scavenging activity than the other extracts. Hexane (CVH) and aqueous ethanol fractions (CVAE) revealed poor antioxidant activity with IC50 values of 824.8 mu g/mL and 610.3 mu g/mL, respectively. On the other hand, among all of the extracts analysed, it was found that phenolic content of CVEA was higher than other extracts. Except for CVAE, other extracts showed antiproliferative activity depending on the dose. Conclusion: According to the obtained results, our finding suggests that CVAE has a migratory effect on fibroblasts and that CVAE might be a potential therapeutic agent for wound healing.
Keywords: Centaurea virgata; antioxidant activity; wound healing; EXTRACT; ANTIOXIDANT